Complementary and alternative medicine (CAM) in medical anthropology: the experience of Malaysian Chinese cancer survivors - W., Vivien C. Yew; Noor Azlan Mohd Noor (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Discussions on socially and culturally dominant values, beliefs and practices pertaining to patient’s health and culture are not isolated but integral to the practice of contemporary clinical medicine. Medical anthropologists play a unique role in redefining and repositioning the application of CAM in biomedical sciences. This article addresses the current state of knowledge regarding the distinction between medical anthropology and complementary and alternative medicine (CAM). Participant observations of, and in-depth interviews with ten Malaysian Chinese women cancer survivors were carried out to study their CAM use during and after cancer treatment. The results provide insights about the patterns of CAM use as well as the social and cultural factors under-pining the choice of CAM used by cancer survivors before and after treatment. The survivors’ preference for CAM use during cancer diagnosis was found to be influenced by their values, beliefs, and practices with respect to five distinct areas, namely, widespread acceptance of a combined Western and Eastern treatment, traditional Chinese philosophy, existential or life threatening situations, social relationships, and positive influences of global networks.